Increased interest with the introduction of fast-track diagnostic pathway is associated with the regionally increased frequency of giant cell arteritis in Poland: a study based on POLVAS registry data - Milchert, Marcin; Wójcik, Krzysztof; Musiał, Jacek; Masiak, Anna; Majdan, Maria; Jeleniewicz, Radoslaw; Tłustochowicz, Witold; Kur-Zalewska, Joanna; Wisłowska, Małgorzata; Lewandowska-Polak, Anna; Makowska, Joanna; Brzosko, Marek (Frontiers in Medicine, 2024)
Slavic population such as this of Poland is considered to have a low prevalence of GCA, although epidemiological data are sparse. The aim of the study was to compare the reported frequency of GCA in various regions of Poland and to analyze the differences between them.We conducted a multicenter, retrospective study of all GCA patients included in POLVAS registrythe first large multicenter database of patients with vasculitis in Poland. The data from POLVAS registry were compared with the reported prevalence provided by national insurer from the corresponding regions.Tenfold increase in the diagnostic rates of GCA was observed in Poland between 2008 and 2019 reaching 8.38 per 100 000 population > 50 years old. It may be attributed to increased interest accompanied by improved diagnostic modalities with introduction of ultrasound based, fast-track diagnostic pathway in some centers. However, regional inequities are present resulting tenfold differences (from 2.57 to 24.92) in reported prevalence between different regions. Corticosteroids monotherapy was the mainstem of treatment.Further cooperation and education is needed to minimize regional inequities. This observational study suggest some potential for further increase of recognizability of GCA and wider use of other than corticosteroids monotherapy treatment regimens. We hope that polish experience might be interesting and serve some guidance for the populations where GCA is underdiagnosed.